Low latitude scintillations: A comparison of modeling and observations within the CIGALA project - Alfonsi, Lucilla; Wernik, Andrzej W.; Materassi, Massimo; Spogli, Luca; Bougard, Bruno; Monico, João Francisco Galera [UNESP] (My University, 2011)
Ionospheric scintillations can seriously jeopardize the reliability of the GNSS signals and consequently can cause significant error or outage on precise positioning applications. The threat is most acute at low latitudes where ionospheric irregularities are more likely to occur resulting in L-band signal scintillations. This paper describes the effort made to model the ionospheric scintillations over the Latin American region in the frame of the CIGALA project funded by the European GNSS Supervisory Authority within the 7th Framework Programme of the European Commission. Comparisons between the low-latitude model of scintillations and observations are here presented and discussed within the project perspectives. © 2011 IEEE.
Keywords: European Commission; GNSS signals; Ionospheric irregularities; Ionospheric scintillation; Latin americans; Low latitudes; Precise positioning; Supervisory authority; Ionospheric measurement; Scintillation